Coethnicity : diversity and the dilemmas of collective action - Habyarimana, James P. (Russell Sage Foundation series on trust., 2009)
"Ethnically homogeneous communities often do a better job than diverse communities of producing public goods such as satisfactory schools and health care, adequate sanitation, and low levels of crime. Coethnicity reports the results of a landmark study that aimed to find out why diversity has this cooperation-undermining effect. The study, conducted in a neighborhood of Kampala. Uganda, notable for both its high levels of diversity and low levels of public goods provision, hones in on the mechanisms that might account for the difficulties diverse societies often face in trying to act collectively."--Jacket